Enzymatic hydrolysis of lignocellulosic biomass for second generation ethanol production - Maitan-alfenas, Gabriela Piccolo (2014)
Second generation ethanol production has great potential to be a sustainable reality, especially in Brazil due to the large amount of available sugarcane bagasse. Pretreatment methods and biomass hydrolysis continue to be the bottlenecks of the overall process, mainly this second step since the enzymes present high costs. Therefore, efforts have been taken to make the process more cost-effective with regards to the discovery of more effective enzymes. New sources of enzymes are continuously encountered and several strategies of enzyme prospection and production have been studied. One strategy used in the search for new and/or more efficient enzymes is comparative genomic analysis of different microorganisms which allows for the screening of several candidates of interest in a short period of time. Moreover, plant-degrading enzymes can be produced by fungi grown on abundantly available low-cost plant biomass. This work was divided in five chapters being the first chapter a current review about second generation ethanol production focused mainly on the saccharification step. Several strategies of enzyme prospection and production were discussed and detailed. In the second chapter, saccharification of acid- and alkali-pretreated sugarcane bagasse was compared using the enzymatic extract from the pathogen fungus Chrysoporthe cubensis and three commercial enzymatic mixtures. For the sugarcane bagasse studied in this work, the alkaline pretreatment promoted the best saccharification yields, where the C. cubensis extract was responsible for the higher release of glucose and xylose when compared to the commercial enzymatic mixtures Furthermore, the C. cubensis extract was able to produce high specific enzyme activities when compared to the commercial cocktails. In the third chapter, the genomic potential of the candidate fungi was evaluated and the most interesting enzymes for sugarcane bagasse hydrolysis were expressed in Aspergillus vadensis. Nine enzymes from three different fungi, Aspergillus terreus, Nectria haematoccoca and Phaeosphaeria nodorum, were successfully cloned and expressed by heterologous system and these enzymes represent a possibility for a better degradation of sugarcane bagasse. -xylosidases were biochemicallycharacterized and showed maxima activity in the pH range 4.5-5.0 and at temperatures of 55-60°C. In the fourth chapter, two xylanases from Aspergillus nidulans previously cloned in Pichia pastoris, here nominated as Xyn1818 and Xyn3613, were expressed, purified and characterized. The optima pH and temperature for Xyn1818 were 7.5 and 60°C while Xyn3613 achieved maximal activity at pH 6.0 and 50°C. Xyn1818 showed to be very thermostable, maintaining 50% of its original activity after 49 hours when incubated at 50°C. Xyn1818 presented higher activity against wheat arabinoxylan while Xyn3613 had the best activity against xylan from beechwood. Saccharification results showed that the commercial enzymatic cocktails were able to release more sugars (glucose and xylose) after supplementation with the xylanases Xyn1818 and Xyn3613 from A. nidulans. Finally, in the fifth chapter, Aspergillus niger and Trichoderma reesei were substrates: wheat straw and sugarcane bagasse. The fungi produced different sets of (hemi-)cellulolytic enzymes which was reflected in an overall strong synergistic effect in releasing sugars during saccharification using the enzyme blends from both fungi. It was observed that removing monosaccharides from the enzyme production media is very important when T. reesei and A. niger enzyme blends are combined to improve plant biomass saccharification.